Research on the spatial effect of foundation pit under asymmetric loads - Xu, Changjie; Lin, Zhaorui; Jiang, Yalong; Shi, Yufeng; Fan, Xiaozhen; Xiong, Zheng; Liu, Yangfeng (Frontiers in Materials, 2022)
Abstract: This research describes the evolution of the spatial effects of foundation pits considering internal support and external loads. Based on the existing concept of “plane strain ratio”, the term “plane strain ratio considering maximum surface settlement” is proposed to characterize the spatial effects of an asymmetric foundation pit. A series of finite element model calculations were carried out using the Nanchang Aixi Lake foundation pit, including 1) the calculation of simulated actual conditions, 2) the calculation of simulated full symmetric load, and 3) the calculation of simulated asymmetric load. The results indicate that for the symmetric condition at 20 kPa and below, the spatial effect range increases as the load increases. For the symmetric condition above 20 kPa, the load has a negligible impact on the spatial effect range. On the side with a larger load under asymmetric loading conditions, the spatial effect of the working condition below 30 kPa is smaller than the corresponding symmetric load. On the side with a smaller load, the spatial effect of the working condition above 80 kPa increases compared with that of the corresponding symmetrical load. Given and verified are the modified fitting equations that take into account the influence range of spatial effect on both sides of the foundation pit under symmetrical and asymmetrical loads.